2008
DOI: 10.1038/emboj.2008.118
|View full text |Cite
|
Sign up to set email alerts
|

A B-Myb complex containing clathrin and filamin is required for mitotic spindle function

Abstract: B-Myb is one member of the vertebrate Myb family of transcription factors and is ubiquitously expressed. B-Myb activates transcription of a group of genes required for the G2/M cell cycle transition by forming the dREAM/Myb-MuvB-like complex, which was originally identified in Drosophila. Mutants of zebrafish B-myb and Drosophila myb exhibit defects in cell cycle progression and genome instability. Although the genome instability caused by a loss of B-Myb has been speculated to be due to abnormal cell cycle pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 48 publications
0
59
1
Order By: Relevance
“…Moreover, B-Myb appears to play a part in maintaining expression of genes such as Sox2 and Oct4 required for pluripotency in ES cells, and when B-Myb is depleted the result is increased differentiation and apoptosis (Tarasov et al, 2008). Although our findings indicate that B-Myb is required for transcription of G 2 /M genes in embryonal cells through complex formation with LINC, a recent report suggests that B-Myb is also involved in a novel complex containing clathrin and filamin that is required for localization of clathrin on the mitotic spindle and stabilization of the kinetochores (Yamauchi et al, 2008). Thus B-Myb may be involved at more than one level in mitosis as well as in maintenance of stem-cell pluripotency, and it will be of interest to discover which of these functions explains the early lethality of the B-Myb-null embryo.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, B-Myb appears to play a part in maintaining expression of genes such as Sox2 and Oct4 required for pluripotency in ES cells, and when B-Myb is depleted the result is increased differentiation and apoptosis (Tarasov et al, 2008). Although our findings indicate that B-Myb is required for transcription of G 2 /M genes in embryonal cells through complex formation with LINC, a recent report suggests that B-Myb is also involved in a novel complex containing clathrin and filamin that is required for localization of clathrin on the mitotic spindle and stabilization of the kinetochores (Yamauchi et al, 2008). Thus B-Myb may be involved at more than one level in mitosis as well as in maintenance of stem-cell pluripotency, and it will be of interest to discover which of these functions explains the early lethality of the B-Myb-null embryo.…”
Section: Discussioncontrasting
confidence: 55%
“…B-Myb is a transcription factor in vertebrate cells and its knockdown by RNAi abolishes the localization of clathrin on mitotic spindles [14]. It was proposed that the B-Myb complex containing clathrin and filamin together contributes to the function of mitotic spindle and normal mitotic progression [14]. Cyclin G-associated kinase (GAK), which was previously known to regulate clathrin in endocytosis, was also found to be required for the localization of clathrin on spindles [19,20].…”
Section: Clathrin and Mitotic Spindle Assemblymentioning
confidence: 99%
“…During the process of spindle assembly, the endocytic protein clathrin has been supposed to be involved [12]. It was found that clathrin is localized on spindle during cell division [10][11][12][13][14]. Clathrin knockdown by RNAi causes defects in spindle assembly, suggesting that clathrin may play a role in spindle assembly.…”
Section: Clathrin and Mitotic Spindle Assemblymentioning
confidence: 99%
See 2 more Smart Citations